Por favor poderiam me ajudar
Seja a soma dada pela expressão.
n
s(n)=∑(3i+3)
i=1 n²
lim s/(n)
0n→∞ vale
Respostas
respondido por:
7
pelo oq eu entendi é :
![s(n)=\sum_{i=1}^{n} \left( \frac{3i+3}{n^2} \right)\\\\s(n)= \frac{3}{n^2} \sum_{i=1}^{n} \left(i+1 \right) \\\\ \boxed{\boxed{s(n)= \frac{3}{n^2} \left[\sum_{i=1}^{n}(i) + \sum_{i=1}^{n}(1)\right ] }} s(n)=\sum_{i=1}^{n} \left( \frac{3i+3}{n^2} \right)\\\\s(n)= \frac{3}{n^2} \sum_{i=1}^{n} \left(i+1 \right) \\\\ \boxed{\boxed{s(n)= \frac{3}{n^2} \left[\sum_{i=1}^{n}(i) + \sum_{i=1}^{n}(1)\right ] }}](https://tex.z-dn.net/?f=s%28n%29%3D%5Csum_%7Bi%3D1%7D%5E%7Bn%7D+%5Cleft%28+%5Cfrac%7B3i%2B3%7D%7Bn%5E2%7D+%5Cright%29%5C%5C%5C%5Cs%28n%29%3D+%5Cfrac%7B3%7D%7Bn%5E2%7D+%5Csum_%7Bi%3D1%7D%5E%7Bn%7D+%5Cleft%28i%2B1+%5Cright%29+%5C%5C%5C%5C+%5Cboxed%7B%5Cboxed%7Bs%28n%29%3D+%5Cfrac%7B3%7D%7Bn%5E2%7D+%5Cleft%5B%5Csum_%7Bi%3D1%7D%5E%7Bn%7D%28i%29+%2B++%5Csum_%7Bi%3D1%7D%5E%7Bn%7D%281%29%5Cright+%5D+%7D%7D)
resolvendo
![\sum_{i=1}^{n}(i) = \frac{(1+n)*n}{2} \\\\r=1\\a_1=1\\a_n = n\\\\ \boxed{S_n= \frac{(a_1+a_n)*n}{2} = \frac{(1+n)*n}{2} } \sum_{i=1}^{n}(i) = \frac{(1+n)*n}{2} \\\\r=1\\a_1=1\\a_n = n\\\\ \boxed{S_n= \frac{(a_1+a_n)*n}{2} = \frac{(1+n)*n}{2} }](https://tex.z-dn.net/?f=%5Csum_%7Bi%3D1%7D%5E%7Bn%7D%28i%29++%3D+%5Cfrac%7B%281%2Bn%29%2An%7D%7B2%7D+++%5C%5C%5C%5Cr%3D1%5C%5Ca_1%3D1%5C%5Ca_n+%3D+n%5C%5C%5C%5C+%5Cboxed%7BS_n%3D+%5Cfrac%7B%28a_1%2Ba_n%29%2An%7D%7B2%7D+%3D+%5Cfrac%7B%281%2Bn%29%2An%7D%7B2%7D++%7D)
temos
![s(n)= \frac{3}{n^2} \left( \frac{(1+n)*n}{2}+n \right)\\\\s(n)= \frac{3}{n}\left( \frac{1+n}{2}+1 \right) \\\\\boxed{\boxed{s(n)= \frac{3n+9}{2n} }} s(n)= \frac{3}{n^2} \left( \frac{(1+n)*n}{2}+n \right)\\\\s(n)= \frac{3}{n}\left( \frac{1+n}{2}+1 \right) \\\\\boxed{\boxed{s(n)= \frac{3n+9}{2n} }}](https://tex.z-dn.net/?f=s%28n%29%3D+%5Cfrac%7B3%7D%7Bn%5E2%7D+%5Cleft%28+%5Cfrac%7B%281%2Bn%29%2An%7D%7B2%7D%2Bn+%5Cright%29%5C%5C%5C%5Cs%28n%29%3D+%5Cfrac%7B3%7D%7Bn%7D%5Cleft%28++%5Cfrac%7B1%2Bn%7D%7B2%7D%2B1++%5Cright%29+%5C%5C%5C%5C%5Cboxed%7B%5Cboxed%7Bs%28n%29%3D+%5Cfrac%7B3n%2B9%7D%7B2n%7D+%7D%7D)
calculando o limite
![\lim_{n \to \infty} \frac{3n+9}{2n} \\\\ = \lim_{n \to \infty} \frac{n*(3+ \frac{9}{n} )}{2n} \\\\ \lim_{n \to \infty} \frac{3+ \frac{9}{n} }{2}= \frac{3+0}{2}= \frac{3}{2} \lim_{n \to \infty} \frac{3n+9}{2n} \\\\ = \lim_{n \to \infty} \frac{n*(3+ \frac{9}{n} )}{2n} \\\\ \lim_{n \to \infty} \frac{3+ \frac{9}{n} }{2}= \frac{3+0}{2}= \frac{3}{2}](https://tex.z-dn.net/?f=+%5Clim_%7Bn+%5Cto+%5Cinfty%7D++%5Cfrac%7B3n%2B9%7D%7B2n%7D+%5C%5C%5C%5C+%3D+%5Clim_%7Bn+%5Cto+%5Cinfty%7D++%5Cfrac%7Bn%2A%283%2B+%5Cfrac%7B9%7D%7Bn%7D+%29%7D%7B2n%7D+%5C%5C%5C%5C+%5Clim_%7Bn+%5Cto+%5Cinfty%7D++%5Cfrac%7B3%2B+%5Cfrac%7B9%7D%7Bn%7D+%7D%7B2%7D%3D+%5Cfrac%7B3%2B0%7D%7B2%7D%3D+%5Cfrac%7B3%7D%7B2%7D+++)
resolvendo
temos
calculando o limite
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás